Covid-19 in Lupus Nephritis - Ramadhan Ananda Putra; Raveinal; Fauzar; Deka Viotra (HM Publisher, 2021)
COVID-19 outbreak is currently being concerned for managing patients withimmunological disorders nowadays, including SLE. Lupus is a complexautoimmune disease characterized by the presence of autoantibodies that againstcell nucleus involved many organs in the body. Patients with SLE will increaserisk of severe infection because the intrinsic respond attack with their immunerespond though immunosuppressive drugs consumption, and will potentiallydamage some organs target associated with their disease. Lupus have multipleclinical manifestations with a fluctuating symptom. Patient who come with thesymptom ofbreathlessness will getworse day by day. The symptom could be felt inthe same time as fatigue, joint pain, hair loss, malar rash, oral ulcer, pleuraleffusion and swollen feet. There's a patient with antinuclear antibody positive foranti-smith and anti-Ro/SS-A. She was diagnosed with COVID-19, SLE withnephritis, haemolytic anemia, vasculitis and pleural effusions. The clinicalmanifestations of this patient indicate a COVID-19 with lupus nephritis that hassevere disease. She was being treated with methylprednisolone andhydroxychloroquine for SLE and azithromycin plus oseltamivir as a therapy forCOVID-19. The effect of hydroxychloroquine on SARS-CoV-2 was better seen inpatients with SLE who gotthe medication regularly. Patients went home after 24days of hospitalization after negative RT-PCR results and clinical improvement ofLES.